Comprehensive thematic T-matrix reference database: a 2017–2019 update. (February 2020) - Mishchenko, Michael I.
Highlights: This compilation lists relevant T-matrix publications on electromagnetic scattering by particles and particle groups that have appeared since 2017. Abstract: Since its inception in the mid-1960s, the T -matrix method has been one of the most versatile and efficient numerically exact computer solvers of the time-harmonic macroscopic Maxwell equations. It has been widely used for the computation of electromagnetic scattering by single and composite particles, discrete random media, periodic structures (including metamaterials), and particles in the vicinity of plane or rough interfaces separating media with different refractive indices. This compilation is the ninth update to the comprehensive thematic database of peer-reviewed T -matrix publications initiated in 2004 and lists relevant publications that have appeared since 2017. It also includes a few earlier publications that have so far been overlooked.